Exploring the Linkages between Website Characteristics, Customer Experience, and Brand Engagement (Revista Galega de Economía)
The prime objective of this research is to investigate the association among website characteristics (information quality, system quality, and perceived security) and customer experience in the online retail context. It also aimed to verify if customer experience has any effect on brand engagement. A questionnaire was utilized for collecting the data from customers of online retailers in the UAE. All responses were quantitatively analyzed via PLS-SEM. The findings showed that information quality positively affect customer experience. It was also found that system quality and perceived security are positively correlated with customer experience. Finally, the analysis verified that customer experience has a positive impact on brand engagement. This paper provides valuable implications to the management in retail industry. The results could be useful for marketing practitioners in e-commerce industry to devise strategies aimed at minimizing the risks in the electronic shopping context, particularly security aspects to attain greater performance.